(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
Central University Libraries in Western India are pivotal hubs for academic and research activities, yet face challenges in meeting modern digital resource demands and user service expectations. This study explores strategies to enhance these libraries' digital infrastructure and user services. Key objectives include evaluating current digital resource availability, identifying gaps in service delivery, and proposing tailored solutions to improve accessibility, usability, and efficiency. By integrating advanced technologies, enhancing digital collections, and optimizing user interfaces, these libraries can better support diverse academic needs and foster a conducive learning environment. The research employs a mixed-methods approach, combining quantitative surveys with qualitative interviews among library users and staff to gather comprehensive insights. Findings aim to inform policy makers, administrators, and librarians on actionable steps to elevate library services, thereby enriching educational experiences and research outcomes across Central Universities in Western India.